Potensi Sari Kurma (Phoenix dactylifera) sebagai Peluruh Kristal Kalsium Oksalat Secara In Vitro - Wilujeng Ayu; Wisnu Cahyo Prabowo; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Dates (Phoenix dactilyfera) contain chemical compositions that can be used as traditional medicine for Calcium oxalate of kidney stone decay. Compound in palm juice can make Calcium oxalate dissolving is flavonoid and calium . The purpose of this study was to determine the effect of Palm dates juice dissolving calcium oxalate to determine the relationship between the concentration of dates palm juice with calcium solubility in kidney stones. To test its activities carried out in vitro using calcium oxalate which incubated for 3 hours with shaken out every 20 minutes at 37oC Determination of the solubility of calcium in date palm juice is by weighs insoluble calcium oxalate. Palm's juice concentration is divided into 60%, 50%, 40%, 30% and 20%. The results of these concentrations can be concluded that the juice of dates has the activity of dissolving calcium oxalate from kidney stones with average result weight in sequence 0.02 + 0.005 g; 0.02 + 0.005 g; 0.03 + 0.005 g; 0.04 + 0.005 g and 0.05 + 0.005 g. Positive control (batugin elixir) 60%, 50%,40%, 30% and 20% with in sequence result 0.08 + 0.001 g; 0.08 + 0.001 g; 0.08 + 0.005 g; 0.09 + 0.005 g; and 0.1 + 0.005 g. Negative Control result 0.11 g. The results obtained from the standard deviation are 0.031. Calcium oxalate that is not dissolved at most in the sample is 20% with an average of 0.05 + 0.005 g and the positive control is 20% of the batugine with an average of 0.1 + 0.005 g.Based on the weighing of calcium oxalate from each concentration the higher the concentration will cause the least insoluble calcium oxalate.